Utilization of Ultrasonography in Dermatology: Two Case Reports of Calcinosis Cutis - Park, Jae Wan; Han, Hye Sung; Jeong, Guk Jin; Hong, Ji Yeon; Park, Kui Young; Seo, Seong Jun (Annals of dermatology, 2022)
Development of newer generation of cost-effective ultrasonic devices in recent years has increased the use of ultrasonography in dermatology. Several lesions can be diagnosed and managed using ultrasonography. Calcinosis cutis involves the deposition of insoluble calcium salts in the cutaneous and subcutaneous tissues. On ultrasonography, it specifically presents as hyperechoic deposits with a posterior acoustic shadowing artifact due to the acoustic properties of calcium. A 62-year-old female patient presented with a solitary, skin-colored, palpable nodule on the inner side of the right lower leg. The lesion was beneath the intact skin and detectable only on palpation. However, ultrasonography demonstrated a clear delineation of the lesion, showing hyperechoic deposits with a posterior acoustic shadow (15 MHz, linear probe). Skin biopsy and curettage were performed, revealing histological features consistent with calcinosis cutis. Four weeks after the procedure, ultrasonography performed to evaluate the outcome of treatment, showed recurrence. Another 18-year-old female patient presented with a skin-colored deep-seated nodule on the left temple. On ultrasonography, linear hyperechoic deposits with a posterior acoustic shadow were visible. Skin biopsy was performed, and histopathologic features showed calcified material in the subcutaneous tissue. These two cases of calcinosis cutis highlight the diagnostic value of ultrasonography in dermatology.